FLDs on need based plant protection in oilseeds: impact in enhancing productivity and profitability under farmers' conditions: FLDs on need based plant protection in oilseeds: impact in enhancing productivity and profitability under farmers' conditions - G D S KUMAR; A SRINIVAS (Journal of Oilseeds Research, 2023)
Frontline demonstrations in oilseed crops were conducted on farmers' fields in different agro-ecological situations on need based plant protection during 2015-16 to 2021-22 to show the productivity potential and profitability of Improved Technologies (IT). The results indicated that, the IT plots recorded higher mean seed yield, gross returns, additional net returns and B:C ratio than the farmers' practice plots indicating the technical and economic feasibility of IT. To speed up the dissemination of plant protection technologies and scale-up the demonstrations, partnerships between extension agencies, state departments of agriculture and input agencies, must be established.